Effect of Boron-Doped Mesoporous Bioactive Glass Nanoparticles on C2C12 Cell Viability and Differentiation: Potential for Muscle Tissue Application - Ege, Duygu; Nawaz, Qaisar; Beltran, Ana M.; Boccaccini, Aldo R. (ACS Biomaterials Science and Engineering, 2022)
Mesoporous bioactive glasses (MBGs) exhibit a high surface area and a highly ordered mesoporous structure. MBGs have potential for both hard and soft tissue engineering applications. MBGs may be doped with biologically active ions to tailor their biological activity. Boron is being widely studied as a dopant of bioactive glasses. Recently, research has demonstrated the potential of boron-containing bioactive glasses for muscle regeneration. In this study, boron-containing MBGs, 10B-MBG and 18B-MBG nanoparticles, were produced by a microemulsion-assisted sol-gel approach for potential muscle regeneration applications. First, X-ray diffraction (XRD), Fourier transform infrared (FTIR), and energy-dispersive X-ray spectroscopy (EDX) analyses were conducted to study the chemical structure and composition of the nanoparticles. To examine the nanoparticle morphology, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images were analyzed. Both SEM images and particle size distribution determined by dynamic light scattering (DLS) indicated a decrease of the average particle size after boron doping. TEM images indicated a slit-shaped mesoporous structure of nanoparticles for all compositions. The ζ potential was measured, and a negative surface charge was found for all study groups due to the presence of silanol groups. Cytocompatibility and fluorescence microscopy studies were also carried out. The results indicated that low concentrations (0.1 and 1 mg mL-1) of all MBG nanoparticles led to high viability of C2C12 cells. Fluorescence microscopy images indicated that at lower nanoparticle concentrations (0.1 and 1 mg mL-1), C2C12 cells appeared to differentiate into myotubes, which was indicated by a spindle-shaped morphology. For 10 mg mL-1concentration of nanoparticles, C2C12 cells had a lower aspect ratio (estimated qualitatively by inspection of the images), which implied a lower degree of differentiation. Boron-doped MBG nanoparticles in reduced concentrations are suitable to induce differentiation of C2C12 cells into myotubes, indicating their potential for applications in muscle tissue repair.
CRIS-Team Scopus Importer:2022-12-23
Keywords: actin; bioactive glass; fluorescence microscopy; MBG; myoblast cell; myotube